THE EFFECT OF WETTING AGENTS ON THE GROWTH OF TUBERCLE BACILLI - Dubos, René J. (The Rockefeller University Press, 1948)
Tween 80 and Triton A20 are two water-dispersible, non-ionic, surface-active agents which favor dispersed growth of tubercle bacilli in aqueous media probably by wetting the bacterial surface. Tween 80 is a polyoxyethylene ester of sorbitan monooleate and is liable to enzymatic hydrolysis by lipases. Triton A20 in an arylalkyl polyether of phenol which appears resistant to the known enzymes of animal tissues. Tween 80 loses its ability to disperse cultures of tubercle bacilli in media containing serum; Triton A20 does not. Tween 80 increases the yield of growth, probably by supplying oleic acid to the bacilli; Triton A20 does not. In concentrations sufficient to cause dispersed browth, Tween 80 (purified by removal of unesterified fatty acid) and Triton A20 are completely innocuous for virulent tubercle bacilli. However, Triton A20 exhibits a marked toxic effect on the avirulent variants of mammalian strains; Tween 80 does not. The two wetting agents also differ in their effects on the morphological aspects of the bacterial cultures. Whereas Triton A20 prevents the formation of large amorphous bacillary clumps, it is less effective in preventing the orientation of the virulent bacilli resulting in the formation of long bacillary strands. Tween 80 on the contrary prevents also the formation of these cords of bacilli and exerts therefore a more effective dispersing effect on cultures of virulent tubercle bacilli.